1990
DOI: 10.2307/281496
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Species of Origin of Residual Blood on Lithic Material

Abstract: The examination of stone-tool edges for blood-antigen residue is a relatively new technique in the archaeological analysis of lithic material. To date, a number of different methods have been employed to determine the species of origin of residual blood, such as Ouchterlony double-diffusion (Ouchterlony 1968) and radioimmunoassays (RIAs) (Lowenstein 1985, 1986). These techniques have been of limited use due to problems of sensitivity, cost, and applicability to archaeological field conditions. Enzyme immunoass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
4

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 11 publications
0
40
0
4
Order By: Relevance
“…biomolecule) survival is in the use of proteins. Immunoassay techniques were initially utilized (Fletcher et al 1984;Hyland et al 1990;Cattaneo et al 1992), but within the past decade an increasing number of applications of soft-ionization mass spectrometry has been developed.…”
mentioning
confidence: 99%
“…biomolecule) survival is in the use of proteins. Immunoassay techniques were initially utilized (Fletcher et al 1984;Hyland et al 1990;Cattaneo et al 1992), but within the past decade an increasing number of applications of soft-ionization mass spectrometry has been developed.…”
mentioning
confidence: 99%
“…A team at the University of Pittsburgh (Hyland, et al, 1990) reports their identification of blood, using the ELISA method, on an 11,000 year-old Paleo-Indian scraper from the Shoop site in Pennsylvania. In this case, the animal was identified as cervid, but it could not be further specified as caribou or deer.…”
Section: Case 7: a Cervid In Late Pleistocene Pennsylvaniacaribou Or mentioning
confidence: 99%
“…We had previously evaluated the anti-human-albumin to ensure that it was not recognising an epitope common to other species (Fletcher et al, 1984;Hyland et al, 1990) or to other serum proteins; we had similarly checked that human material did not cross-react with monoclonal antibovine-albumin. We are thus confident that a positive result in this study reliably indicated the specimen's human origin.…”
Section: Dilutions Of Monoclonal Anti-human Albuminmentioning
confidence: 99%
“…The first workers were generally interested in the extraction of protein from ancient human bone; they succeeded in identifying collagen and albumin in fossil bone using radio-immuno assay (RIA) (Lowenstein, 1981) and in detecting haemoglobin in Roman, Iron Age, and Copper Age human bone by an immunoblotting technique (Ascenzi et al, 1985). Enzymelinked immunosorbent assays (ELISA) have recently been used to detect cervid blood on lithic artifacts (Hyland et al, 1990), human haemoglobin in bone (Smith and Wilson, 1990) and human albumin in Australian Palaeolithic rock-art (Loy et al, 1990). However, none of these studies seems to have met all the requirements necessary for this type of work, namely sensitivity, specificity, replicability, safety, and consistent use of adequate control samples.…”
mentioning
confidence: 99%